Bilateral Intraosseous Migration of Mandibular Second Premolars in a Patient with Nine Missing Teeth - H. Shahoon; M. Esmaeili (Tehran University of Medical Sciences, 2010)
Intraosseous migration is an unusual developmental dental anomaly, which demonstrates horizontal movement of unerupted teeth only affecting the permanent dentition of the lower jaw. Mandibular second premolar is the most common impacted tooth after the third molars and maxillary canines. Distal migration of the second premolar is rare and early loss of the permanent first molar is one of the most important predisposing factors of intrabony migration of this tooth. Bilateral migration of the mandibular premolars is very rare compared to unilateral migration. Hereby, we present an 18-year-old man with bilateral intrabony migration of the mandibular second premolars to the mandibular angle (at the inferior and buccal side of the mandibular canal) in the presence of first molars. The patient also had nine congenitally missing teeth without any systemic complication or abnormality in the skeleton. The teeth were surgically extracted. The clinical and diagnostic features and treatment of this case are discussed.